Integrated policymaking: Institutional designs for implementing the sustainable development goals (SDGs) - Breuer, Anita; Leininger, Julia; Malerba, Daniele; Tosun, Jale (World development, 2023)
Increased policy coherence and integrated implementation are necessary to address pressing development problems that cut across different sectors. Meeting these demands, as called for by the 2030 Agenda for Sustainable Development, requires institutional innovation. Based on the comparative analysis of 137 countries, this paper investigates how governments have responded to this call and which contextual factors shape their institutional responses. We propose a four-dimensional typology to analyse the institutional set-ups for implementing the Sustainable Development Goals (SDG), focusing on political leadership, horizontal integration across policy sectors, vertical integration across levels of government, and integration of societal stakeholders. We apply this framework to the descriptions of national SDG-implementation bodies provided by governments in their Voluntary National Review (VNRs) and use qualitative directed content analysis and regression modelling to investigate different driving factors of institutional design choices, including socio-economic development and political regime. Besides a strong commitment from the Centre of Government in most cases, our results show that ministries of the exterior and the environment have a dominant role, indicating that sustainability is not yet perceived holistically. Further, we find that the integration of subnational governments and societal actors is often under-institutionalised: while countries with higher levels of socio-economic development appear more likely to set up mechanisms suited to achieving cross-sectoral integration, political regime type seems to have little impact on institutional design choices for SDG implementation. Conceptually, this study offers a theory-led investigation of the institutional mechanisms for integrated SDG-implementation and the factors that drive institutional innovation or inertia. Empirically, by compiling the information in an original dataset, our study paves the way for future cross-national analysis on effective integrated SDG implementation and identifies entry points for inter- and transnational support of integrated SDG implementation in the context of development cooperation.